Supramolecular hydration structure of graphene-based hydrogels: density functional theory, green chemistry and interface application - Hon Nhien Le; Duy Khanh Nguyen; Minh Triet Dang; Huyen Trinh Nguyen; Thi Bang Tam Dao; Trung Do Nguyen; Chi Nhan Ha Thuc; Van Hieu Le (Beilstein Journal of Nanotechnology, 2025)
Natural hydration shells are discovered to play an essential role in the structure and function of biomolecules (deoxyribonucleic acid, protein, and phospholipid membrane). Hydration layers are also important to the structure and property of artificial graphene-based materials. Our recent works prove that graphene-based hydrogels are supramolecular hydration structures that preserve graphene nanosheets from the restacking through hydrophobic force, van der Waals force, and π–π interaction. In this manuscript, density functional theory and high-performance computing (HPC) are used for modeling and calculating van der Waals force between graphene nanosheets in water-intercalated AB bilayer graphene structures. A layer of water molecules significantly decreases the intersheet van der Waals force. A novel hydrogel of graphene oxide–silica gel–zinc hydroxide (GO-SG-ZH) is experimentally synthesized to demonstrate the advantages of hydrated hydrogel structure in comparison with dry powder structure. The synthesis of graphene-based hydrogels is a green chemistry approach to attain extraordinary properties of graphene-based nanostructures. Analytical characterizations exhibited moisture contents, water evaporation rates, three-dimensional structures, elemental compositions, aqueous dispersibility, and antibacterial activities. Hydration shells on graphene-based nanosheets in the hydrogel increase intersheet distances to prevent the stacking of the nanostructures. Hydration layers in the GO-SG-ZH hydrogel was also lubricative for direct brush coating on polymer substrates, typically polylactide films. Interfacial adhesion of graphene-based nanosheets on polylactide substrates made the antibacterial coating stable for several application purposes. In general, supramolecular graphene-based hydrogels are bioinspired hydration structures to advance nanoscale properties and nanotechnology applications.